2013
DOI: 10.1093/icvts/ivt383
|View full text |Cite
|
Sign up to set email alerts
|

Does tranexamic acid stop haemoptysis?: Table 1:

Abstract: A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was 'Does tranexamic acid stop haemoptysis'? Altogether 49 papers were found using the reported search strategy, of which 13 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. This consisted of one systematic review including a meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 13 publications
0
27
0
2
Order By: Relevance
“…Mild and moderate haemoptysis usually responds to tranexamic acid (typically 500 mg three times daily), although not licensed for this indication (SoR A and QoE III) [118,119]. Tranexamic acid interferes with clot dissolution because it inhibits fibrinolysis and so increases infarction potential.…”
Section: Follow-upmentioning
confidence: 99%
“…Mild and moderate haemoptysis usually responds to tranexamic acid (typically 500 mg three times daily), although not licensed for this indication (SoR A and QoE III) [118,119]. Tranexamic acid interferes with clot dissolution because it inhibits fibrinolysis and so increases infarction potential.…”
Section: Follow-upmentioning
confidence: 99%
“…Systemic tranexamic acid is associated with thromboembolic complications. (13,14) Nebulized tranexamic acid could potentially achieve rapid control of hemoptysis without systemic side effects. A recent randomized controlled trial reported the successful use of nebulized tranexamic acid for moderate hemoptysis (10) due to bronchiectasis, infection, or malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…If the bleeding site is known, laying the patient in the lateral decubitus position on the side of the haemorrhage may help. Tranexamic acid may reduce bleeding duration and volume,2 but identifying the bleeding source may be critical in permitting life-saving treatment 3. Once the patient is stabilised, CT angiography can be used to identify the site of bleeding.…”
Section: Descriptionmentioning
confidence: 99%